OEsophageal Ion Transport Mechanisms and Significance Under Pathological Conditions - Becskeházi, Eszter; Korsós, Marietta Margaréta; Erőss, Bálint; Hegyi, Péter; Venglovecz, Viktória (Frontiers in Physiology, 2020)
Ion transporters play an important role in several physiological functions, such as cell volume regulation, pH homeostasis and secretion. In the oesophagus, ion transport proteins are part of the epithelial resistance, a mechanism which protects the oesophagus against reflux-induced damage. A change in the function or expression of ion transporters has significance in the development or neoplastic progression of Barrett’s oesophagus (BO). In this review, we discuss the physiological and pathophysiological roles of ion transporters in the oesophagus, highlighting transport proteins which serve as therapeutic targets or prognostic markers in eosinophilic oesophagitis, BO and oesophageal cancer. We believe that this review highlights important relationships which might contribute to a better understanding of the pathomechanisms of oesophageal diseases.